Digital transformation in the tourism sector: the key role of social networks (2024)
The research seeks to establish the use of social networks in companies in the tourism sector, especially to identify the most popular networks, their type and the role they play in these companies. The problem was approached through a systematic literature review, focused on the use of social networks in tourism companies. The Scopus database was consulted, initially finding 179 articles, using the keywords: social media, tourism and hotels. After applying the exclusion criteria, 15 articles were identified. The findings indicate that the Tripadvisor network, specialized in the tourism sector, is the most used, followed by Facebook and Twitter, which are generalist networks. It is concluded that social networks have transformed the way in which users in the hotel sector interact, research and make decisions about their accommodations, consulting the opinions and previous experiences of other users.